The small DNA binding domain of λ integrase is a context-sensitive modulator of recombinase functions - Sarkar, Dibyendu (Oxford University Press, 2001)
λ Integrase (Int) has the distinctive ability to bridge two different and well separated DNA sequences. This heterobivalent DNA binding is facilitated by accessory DNA bending proteins that bring flanking Int sites into proximity. The regulation of λ recombination has long been perceived as a structural phenomenon based upon the accessory protein-dependent Int bridges between high-affinity arm-type (bound by the small N-terminal domain) and low-affinity core-type DNA sites (bound by the large C-terminal domain). We show here that the N-terminal domain is not merely a guide for the proper positioning of Int protomers, but is also a context-sensitive modulator of recombinase functions. In full-length Int, it inhibits C-terminal domain binding and cleavage at the core sites. Surprisingly, its presence as a separate molecule stimulates the C-terminal domain functions. The inhibition in full-length Int is reversed or overcome in the presence of arm-type oligonucleotides, which form specific complexes with Int and core-type DNA. We consider how these results might influence models and experiments pertaining to the large family of heterobivalent recombinases.